The Effect of Banana Flour and Mangosteen Skin Flour on The Organoleptic Properties of Brownies - Hasanah, Irfatul; Awidiyantini, Ruly (TAPE : Jurnal Teknologi Hasil Pertanian, 2024)
Banana Flour and Mangosteen Peel Flour are flours with nutritional content that is not inferior to the nutritional content of wheat flour. One of the uses is to use the flour as an ingredient for making brownies. The purpose of this study is to determine the Effect of Banana Flour and Mangosteen Peel Flour on the Organoleptic Characteristics of Brownies. The method used in this study used a Complete Random Design (RAL) with 4 treatments and 6 repeaters. Data analysis uses the ANOVA One Way Test and continues with the Duncan Test. Based on the analysis of the data of the results of the organoleptic test which included color, aroma, taste and texture carried out on 25 panelists, the average panelist liked brownies in P1 using a comparison of 100 grams of banana flour and 100 grams of mangosteen peel flour. As for the OneWay Anova analysis test, the color, aroma and texture results are p > 0.05 so it can be said that there is no real difference to brownies. Meanwhile, the results of One Way Anova on the brownie flavor have a significance of p < 0.05 so that it can be said that there is a real difference in brownies and can be further tested with the Duncan Test which produces P0 with P3, P2 and P1 there is a real difference in brownie taste. Therefore, the use of banana flour and mangosteen peel flour affects the taste of brownies.